Impact of Dental Rehabilitation Under General Anesthesia on Oral Health-Related Quality-of-Life and Dental Anxiety in Turkish Children - Gülsüm Duruk; Raziye Kuru; Ahmet Selim Özkan (Association of Support to Oral Health Research (APESB), 2021)
Objective: To analyze children's and parents' oral health-related quality of life (OHRQoL) and children's dental fears before and after the dental rehabilitation under general anesthesia (DRGA). Material and Methods: 104 parents and their 3 to 13-year-old children (5.90 ± 2.42) who received DRGA were surveyed before and after DRGA. The children were divided into two groups: Group 1 - healthy children (n=43) and Group 2 - children with medical problems (n=61). After recording their socio-demographic information, parents completed a self-administered questionnaire named Early Childhood Oral Health Impact Scale (ECOHIS), which includes two main parts - Child Impact Section (CIS) and Family Impact Section (FIS). On the other hand, the children received a dentist-administered questionnaire named Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) and Frankle Behavior Scale (FBS). For statistical analyses, Wilcoxon Signed-Rank, Mann Whitney-U, Kruskal-Wallis, and Spearman's Correlation tests were used. Results: A statistically significant decrease in all CIS, FIS, ECOHIS and CFSS-DS scores was observed after DRGA (p<0.01). This decline was greater in healthy children than in children with systemic problems (p<0.01). Conclusion: Children's and parents' OHRQoL showed better results after DRGA. The decreases in dental anxiety in children were observed after DRGA.